Tracheo-oesophageal anomalies in the Goldenhar anomalad. Issue 2 (April 1985) - Mendelberg, A; Ariel, I; Mogle, P; Arad, I
Abstract : A case of the Goldenhar anomalad is presented with a previously undescribed association with oesophageal atresia and tracheo-oesophageal fistula. This is the second instance of a tracheobronchial-oesophageal communication being found in association with the anomalad. Awareness of this combination may facilitate future diagnosis and treatment of the anomaly.